Allum F. and Gilmour S. (eds., 2019), Elgar Handbook of Organised Crime and Politics, Cheltenham, UK: Edward Elgar, ISBN: 9781786434562. - Attilio Scaglione (Coordinamento SIBA, 2019)
For Book Reviews Abstract is not Required